Penguatan Kesadaran Keamanan Siber melalui Edukasi Pencegahan Phishing pada Remaja Gereja Katolik Paroki St. Petrus Remu Sorong - Melda Agnes Manuhutu; Yohvita Yohvita; Rionaldy Rionaldy; Ira Ira; Tesyal Tesyal; Nelce Nelce; Riskye Riskye; Adrianu Adrianu; Revan Revan (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This community service activity was conducted at the Catholic Parish Church of St. Petrus Remu Sorong with the aim of providing cyber crime education focusing on phishing prevention and countermeasures for youth members aged between 13–18 years. The program was implemented through six systematic stages: preparation, socialization, training, technology application, mentoring and evaluation, and program continuity. A total of 11 participants from junior and senior high school levels attended the activity held on Saturday, April 25, 2026, at Aula Jhonatan Fatem. Interactive methods were employed including presentations, discussions, real-case phishing simulations, link analysis exercises, two-factor authentication setup, and quiz evaluations. Results showed that participants became aware of phishing dangers, were able to identify suspicious messages and fake links, and a small digital education group was formed for program continuity. This activity is expected to build a sustainable cyber security culture among the youth community of the church in Sorong.